2013
DOI: 10.1186/1179-5395-43-3
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of high purity genomic DNA from pine for use in a high-throughput Genotyping Platform

Abstract: Standard protocols for extracting genomic DNA from Pinus radiata D. Don needles, such as CTAB-based methods, can yield large quantities of DNA. However, final DNA purity can be an issue due to carry over of contaminants that can impede accurate high throughput genotyping. This study evaluated eight DNA extraction and purification protocols to determine which method provided the greatest improvement in call rates and accuracy when using the Sequenom iPLEX W Gold MassARRAY W genotyping technology. Of the methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Thechaotropic agents (for instance guanidinium thiocyanate) used in this method would have played a role to remove DNA-binding proteins, allowing for better absorption in the spin columns (Boom et al 1989). The results confirmed that the use of cell lysis buffer and following elution over a column could greatly enhance the amount of the extracted pure mDNAs, which was previously reported also by other researchers (Poh and Gan 2014;Telfer et al 2013). In addition to the technical efficiency, the SCB protocol is significantly more cost-effective (∼ US$ 1 per reaction) compared with the commercial kits (∼ US$ 7 per reaction), which makes this method suitable for molecular biology studies, such as PCR amplifications.…”
Section: Discussionsupporting
confidence: 90%
“…Thechaotropic agents (for instance guanidinium thiocyanate) used in this method would have played a role to remove DNA-binding proteins, allowing for better absorption in the spin columns (Boom et al 1989). The results confirmed that the use of cell lysis buffer and following elution over a column could greatly enhance the amount of the extracted pure mDNAs, which was previously reported also by other researchers (Poh and Gan 2014;Telfer et al 2013). In addition to the technical efficiency, the SCB protocol is significantly more cost-effective (∼ US$ 1 per reaction) compared with the commercial kits (∼ US$ 7 per reaction), which makes this method suitable for molecular biology studies, such as PCR amplifications.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the high level of PCR sensitivity obtained with genomic DNA in these assays, the low detection rates observed for C. minus from pine needles may indicate that the DNA extraction method used may not be efficient enough for pathogen detection from P. radiata. Obtaining high-quality DNA from pine needle samples can be difficult due to high amounts of co-contaminants (Telfer et al 2013). Comparisons of DNA extraction methods have been performed to identify the best method for obtaining high-quality DNA for PCR from P. radiata (Ioos et al 2010;Telfer et al 2013), and these methods should be tested for improved detection of C. minus from infected pine needles.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extractions from leaves were performed using the NucleoSpin® Plant II 96 kit (Macherey Nagel, Duren, Germany; Telfer et al, 2013) implemented on a Tecan Genesis 200RMP (Tecan, Maennedorf, Switzerland) liquidhandling robot. In short, two 1 cm² fresh or frozen leaves were homogenized in a 2 ml microcentrifuge tube using the TissueLyser (Qiagen, Venlo, Netherlands).…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%